1998
DOI: 10.1098/rspb.1998.0349
|View full text |Cite
|
Sign up to set email alerts
|

The role of parasite–induced immunodepression, rank and social environment in the modulation of behaviour and hormone concentration in male laboratory mice (Mus musculus)

Abstract: Peripheral immune responsiveness in male laboratory mice was reduced by infection with the trichostrongyloid nematode Heligmosomoides polygyrus. Responsiveness was also lower among high-ranking (aggressive) males regardless of infection status. Reduced responsiveness in both infected animals and high rankers was associated with elevated serum corticosterone concentration (a potential immunodepressant) and was compounded among high-ranking males by subsequent high aggressiveness. As in previous experiments, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…There was demonstrated in study on the outbred male mice CFLP that high aggressiveness and high level of blood testosterone in dominants coincided with low immunoresponsiveness and with high susceptibility to infection with blood parasite Babesia microti [111,112]. The positive correlation between aggressiveness and parasite ability was found in CFLP mice under experimental infection with Heligmosomoides polygyrus [113]. The directly opposite results were received in study of the inbred mice C57Bl.…”
Section: Showiness Dominance and Immunocompetencementioning
confidence: 51%
“…There was demonstrated in study on the outbred male mice CFLP that high aggressiveness and high level of blood testosterone in dominants coincided with low immunoresponsiveness and with high susceptibility to infection with blood parasite Babesia microti [111,112]. The positive correlation between aggressiveness and parasite ability was found in CFLP mice under experimental infection with Heligmosomoides polygyrus [113]. The directly opposite results were received in study of the inbred mice C57Bl.…”
Section: Showiness Dominance and Immunocompetencementioning
confidence: 51%
“…Furthermore, this endocrine imbalance may be considered as an adaptive response of the host (Wedekind and Folstad 1994) that, with the help of acquired immunity, accounts for the low parasitemia which characterizes a recrudescence. In fact, in accordance with the adaptive modulation hypothesis first postulated for parasite-mediated sexual selection (Folstad and Karter 1992), several authors have suggested that rodents may regulate testosterone profiles to balance the competing demands of immunity and reproduction (Klein et al 1997;Barnard, et al 1998).…”
Section: Discussionmentioning
confidence: 83%
“…A further mechanism involved in the lower occurrence of allergic reaction in parasitized individuals, which might also account for our observation of shorter duration of edema in A. costaricensis-infected rats, is overproduction of anti-inflammatory corticosteroid hormones (24,25) induced by the helminth infection. However, in our model, we did not find any alteration in serum corticosterone level in A. costaricensis-infected rats even after allergic challenge, indicating that yet another mechanism should underlie the curtailment of allergic edema noted in infected animals in our model.…”
Section: Discussionmentioning
confidence: 91%